The development of atypical haemolytic-uraemic syndrome is influenced by susceptibility factors in factor H and membrane cofactor protein: evidence from two independent cohorts. Issue 11 (22nd March 2005) - Fremeaux-Bacchi, V; Kemp, E J; Goodship, J A; Dragon-Durey, M-A; Strain, L; Loirat, C; Deng, H-W; Goodship, T H J
Abstract : Background: In both familial and sporadic atypical haemolytic-uraemic syndrome (aHUS), mutations have been reported in regulators of the alternative complement pathway including factor H (CFH), membrane cofactor protein (MCP), and the serine protease factor I (IF). A characteristic feature of both MCP and CFH associated HUS is reduced penetrance and variable inheritance; one possible explanation for this is that functional changes in complement proteins act as modifiers. Objective: To examine single nucleotide polymorphisms in both CFH and MCP genes in two large cohorts of HUS patients (Newcastle and Paris). Results: In both cohorts there was an association with HUS for both CFH and MCP alleles. CFH and MCP haplotypes were also significantly different in HUS patients compared with controls. Conclusions: This study suggests that there are naturally occurring susceptibility factors in CFH and MCP for the development of atypical HUS.